Właściwości płytkich gleb pobagiennych na kredzie jeziornej oraz ocena składu chemicznego wód gruntowych = Properties of post-bog soils developed on lacustrine chalk and rate ground soil water properties - Jarnuszewski, Grzegorz; Meller, Edward (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Shallow post-bog soils on lacustrine chalk are characterised by a specific texture connected with their two-stage genesis. Ongoing muck-formation process affects physicochemical and chemical properties of surface horizon of organogenic soils. The material on which the soils developed is of great importance as well as their use and moisture.
Keywords: gleby pobagienne; kreda jeziorna; wody gruntowo-glebowe; właściwości chemiczne gleb; post-bog soils; ground-soil waters; lacustrine chalk; soil chemicalproperties